The Development of Legal Education in the Kingdom of Saudi Arabia - muamar hasan salameh; Jaida Aboul Fotouh (Universitas Lampung, 2017)
In the Kingdom of Saudi Arabia (KSA), Islamic Shariah is the foundation of the laws of the state. While the modern Saudi legal system encompasses both written and unwritten laws, Shariah is still considered supreme and hence directs most of the state’s regulations. Nevertheless, currently, those who aim to practice law need to acquire a foundation of all prevailing laws. Due to the supremacy of Shariah, most universities still do not offer comprehensive degree plans, which often poses limitations to the development of legal education in the Kingdom. This study aims to address this conundrum by examining the various degree plans in Saudi universities, scrutinizing whether they offer comprehensive degrees, which should encompass both Shariah laws yet also the newly codified rules. This research draws upon secondary sources, which analyze the progress of the legal education in KSA and its effects on future legal practitioners. Results suggest that the legal curricular should be redesigned to improve the capabilities of prospective legal professionals by integrating the non-codified rules of law with the Islamic law in a more practical, realistic and efficient manner. Keywords: Legal education, Shariah, Saudi Arabia.